Strategic information systems engineering and management: a ‎framework for integrating organizational design and ‎marketing to enhance enterprise economic potential - Foshchii, Petro; Kovshik , Valentin; Shapovalova , Inga; Oslopova , Maryna; Kosenko , Yaroslav; Matvienko, Vitalii (International Journal of Basic and Applied Sciences, 2025)
Modern enterprises face increasing complexity in aligning organizational structures, marketing initiatives, and operational capabilities to ‎maximize economic potential. This article addresses the critical role of Information Systems (IS) Engineering and Management in achieving ‎this strategic alignment. We move beyond viewing informatics merely as data analysis, proposing instead a conceptual framework ‎engineered to integrate organizational design principles and data-driven marketing strategies through robust information systems. This ‎framework emphasizes requirements engineering, agile IS architecture, business process integration, and effective IS governance as crucial ‎enablers. By synthesizing literature from IS engineering, management science, applied technology, and marketing, we outline the ‎components of this framework and its potential impact on enhancing decision-making agility, optimizing resource allocation, improving ‎customer engagement, and ultimately boosting sales effectiveness and economic potential. The discussion explores implementation ‎challenges from an IS management perspective, including technological adoption, change management, and skill requirements for leveraging ‎applied technologies like AI and advanced analytics within the framework. This work provides a theoretically grounded model for managers ‎and IS professionals aiming to architect and manage integrated systems for sustained competitive advantage‎.
Keywords: Information Systems Engineering; Information Systems Management; Organizational Design; Marketing Strategy; Strategic Alignment, ‎Enterprise Perfor-mance; Applied Technology; Business Process Integration; IT Governance